Philosophy and salvation an essay on wisdom, beauty, and love as the goal of life - Blanco, Carlos (Cambridge : Lutterworth Press, 2013)
We all seek salvation, claims Blanco, because we all become prisoners of negativity. Humanity wants to be saved, we want to overcome the negativity that so often enslaves us. But, where is the saviour to be found, and where is the source of salvation?In Philosophy and Salvation Blanco argues that salvation may only come from the infinite springs of the word. 'The word saves us: the word of science, the word manifested in art, the word of a society which promises something for itself ... Humanity understands itself through language: human beings use words in order to know each other and to co.
pt. 1. In search of fundamentum -- pt. 2. Fundamentum in history -- pt. 3. Questioning as salvation.
"First published 2012"--Title page verso.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Salvation -- Philosophy; Philosophy and religion; Philosophy and religion; Salvation -- Philosophy; PHILOSOPHY -- Movements -- Humanism; Christianity -- Philosophy; Salvation -- Christianity; PHILOSOPHY / General; Electronic books